2019
DOI: 10.1093/femsec/fiz189
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cyanobacteria at the Alaska North Slope with description of two new genera: Gibliniella and Shackletoniella

Abstract: The diversity of cyanobacteria along the Alaskan North Slope was investigated. We isolated and cultivated 57 strains of cyanobacteria and sequenced a section of their rRNA operon containing a fragment of the 16S rRNA gene. Here, we describe 17 found species belonging mainly to families Coleofasciculaceae, Microcoleaceae, Oculatellaceae, Leptolyngbyaceae and to the order Synechococcales. In pursuing a conservative polyphasic approach, we utilized suggested thresholds in 16S rRNA gene differences in parallel wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Leptodesmis is a newly described genus based on environmental, morphological, and molecular data (Raabova et al, 2019). Two species in this genus have been studied, L. alaskaensis (Strunecky et al, 2020) and L. paradoxa (Raabova et al, 2019). In our previous study, we isolated a Leptodesmis strain, A121, from an Erdaoqiao hot spring, Sichuan, China (Tang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Leptodesmis is a newly described genus based on environmental, morphological, and molecular data (Raabova et al, 2019). Two species in this genus have been studied, L. alaskaensis (Strunecky et al, 2020) and L. paradoxa (Raabova et al, 2019). In our previous study, we isolated a Leptodesmis strain, A121, from an Erdaoqiao hot spring, Sichuan, China (Tang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and anatomy traits are the main criteria for classifying and identifying cyanobacteria. Recent studies have shown that traditional cyanobacterial "morphospecies" are comprised of different taxonomic species [3][4][5][6][7]. On the other hand, many cyanobacterial taxa do not have gene sequence data.…”
Section: Introductionmentioning
confidence: 99%
“…That method, as a tool for next generation sequencing (NGS), will be able to uncover cyanobacterial diversity of natural assemblages. Currently, NGS results provide a high number of abstract organizational taxonomic units [4]. Unidentified units cannot be used for ecological or geographical tional taxonomic units [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019, Strunecky et al. 2019), leading to the description of many novel genera such as Plectolyngbya, Nodosilinea, Pantanalinema , Alkalinema , Oculatella, Scytolyngbya, Thermoleptolyngbya, Onodrimia, Timaviella , Toxifilum, and Amazoninema (Perkerson et al. 2011, Taton et al.…”
mentioning
confidence: 99%